Adeno-associated virus in the liver: natural history and consequences in tumour development. Issue 4 (2nd August 2019) - La Bella, Tiziana; Imbeaud, Sandrine; Peneau, Camille; Mami, Iadh; Datta, Shalini; Bayard, Quentin; Caruso, Stefano; Hirsch, Theo Z; Calderaro, Julien; Morcrette, Guillaume; Guettier, Catherine; Paradis, Valerie; et al.
Abstract : Objective: Adeno-associated virus (AAV) is a defective mono-stranded DNA virus, endemic in human population (35%–80%). Recurrent clonal AAV2 insertions are associated with the pathogenesis of rare human hepatocellular carcinoma (HCC) developed on normal liver. This study aimed to characterise the natural history of AAV infection in the liver and its consequence in tumour development. Design: Viral DNA was quantified in tumour and non-tumour liver tissues of 1461 patients. Presence of episomal form and viral mRNA expression were analysed using a DNAse/TaqMan-based assay and quantitative RT-PCR. In silico analyses using viral capture data explored viral variants and new clonal insertions. Results: AAV DNA was detected in 21% of the patients, including 8% of the tumour tissues, equally distributed in two major viral subtypes: one similar to AAV2, the other hybrid between AAV2 and AAV13 sequences. Episomal viral forms were found in 4% of the non-tumour tissues, frequently associated with viral RNA expression and human herpesvirus type 6, the candidate natural AAV helper virus. In 30 HCC, clonal AAV insertions were recurrently identified in CCNA2, CCNE1, TERT, TNFSF10, KMT2B and GLI1 / INHBE . AAV insertion triggered oncogenic overexpression through multiple mechanisms that differ according to the localisation of the integration site. Conclusion: We provided an integrated analysis of the wild-type AAV infection in the liver with the identification of viral genotypes, molecular forms, helper virus relationship and viral integrations. Clonal AAV insertions were positive selected during HCC development on non-cirrhotic liver challenging the notion of AAV as a non-pathogenic virus.